2009
DOI: 10.1002/lt.21920
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of renal function after the switch from a calcineurin inhibitor to everolimus in liver transplant recipients with chronic renal dysfunction

Abstract: Chronic renal dysfunction is a frequent and severe complication in solid-organ transplant recipients. Calcineurin inhibitors (CNIs) are the main pathogenic factors of renal dysfunction. Switching from CNIs to nonnephrotoxic drugs, such as mammalian target of rapamycin inhibitors (everolimus and sirolimus), can improve renal function in these patients, but available data about the efficacy and safety of everolimus in liver transplant recipients are scarce. Twenty-one liver transplant recipients (19 males, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 22 publications
1
44
0
2
Order By: Relevance
“…Previous reports have described no rejection episodes after the introduction of everolimus, [19][20][21] but in 2 trials in which CNI therapy and adjuvant immunosuppressants were withdrawn relatively aggressively, the rates of rejection were 7% 18 and 10%. 17 In the current study, in which there were no protocol-specified withdrawals of other agents, there was a very low rate of acute rejection (<2.0%).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous reports have described no rejection episodes after the introduction of everolimus, [19][20][21] but in 2 trials in which CNI therapy and adjuvant immunosuppressants were withdrawn relatively aggressively, the rates of rejection were 7% 18 and 10%. 17 In the current study, in which there were no protocol-specified withdrawals of other agents, there was a very low rate of acute rejection (<2.0%).…”
Section: Discussionmentioning
confidence: 88%
“…Single-arm studies have demonstrated that maintenance liver transplant patients can be converted from CNIs to everolimus safely at later time points with a low rate of acute rejection. [17][18][19][20][21][22] Like kidney transplant recipients, 23 liver transplant recipients with kidney dysfunction apparently need to be switched from CNI immunosuppression to everolimus either early after transplantation 16 or before the establishment of severe dysfunction. 17 In clinical practice, some centers now initiate everolimus in maintenance liver transplant patients who develop kidney dysfunction or, less frequently, posttransplant neoplasms and attempt to withdraw CNI therapy.…”
mentioning
confidence: 99%
“…In a retrospective observational study, Saliba et al [26] found the improvement in renal function to be greater when conversion to EVR was within first year post-LT (eGFR increased from 77.5 to 90.0 mL/min, P = 0.04) vs those who were converted beyond 1 year post-LT (eGFR increased from 59.1 to 64.6 mL/min, P = 0.01) [26] . The findings Castroagudín et al [25] reported in a retrospective study echoed the less remarkable renal improvement (eGFR improved by 7.7 mL/min at month 12) when conversion to EVR occurred at 5.2 ± 3.1 years from transplant. Thus, the best time point for conversion to EVR for optimal renoprotective effect is still unclear and further studies are warranted.…”
Section: Renoprotective Effectmentioning
confidence: 77%
“…По данным некоторых исследований, использова-ние иммуносупрессивного протокола с эверолиму-сом и отменой ИКН обеспечивало лучшую функ-цию почек без повышения риска отторжения [15]. Однако в проспективном рандомизированном мно-гоцентровом исследовании в течение 6 мес.…”
Section: Discussionunclassified